2007
DOI: 10.1002/pits.20228
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of the concurrent validity of reading comprehension rate: A direct, dynamic measure of reading comprehension

Abstract: Reading comprehension rate (RCR) is a direct measure of reading skills that may be useful in formatively evaluating students reading beyond the fourth-grade level. To investigate the concurrent validity of RCR, we correlated RCR, reading comprehension level (RCL), and words correct per minute (WC/M) with the Broad Reading Cluster Scores of the Woodcock-Johnson III Tests of Achievement (WJ-III ACH ) across 88 students in 4th, 5th, and 10th grades. Results showed that aloud-RCR was significantly correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Research with students in the elementary grades strongly supports the use of WCPM as a sensitive, valid, and reliable measure (Deno, Mirkin, & Chiang, 1982;Espin & Foegen, 1996;Fuchs & Deno, 1991;Fuchs, Fuchs, & Maxwell, 1988;Hintze, Shapiro, Conte, & Basile, 1997); however, this measure is not as sensitive as students' skills develop beyond the fourth-or fifth-grade level Jenkins & Jewell, 1993;Neddenriep, Hale, Skinner, Hawkins, & Winn, 2007). There may be several contributing factors to this decrease in sensitivity as students' reading levels increase.…”
Section: Wcpmmentioning
confidence: 88%
See 1 more Smart Citation
“…Research with students in the elementary grades strongly supports the use of WCPM as a sensitive, valid, and reliable measure (Deno, Mirkin, & Chiang, 1982;Espin & Foegen, 1996;Fuchs & Deno, 1991;Fuchs, Fuchs, & Maxwell, 1988;Hintze, Shapiro, Conte, & Basile, 1997); however, this measure is not as sensitive as students' skills develop beyond the fourth-or fifth-grade level Jenkins & Jewell, 1993;Neddenriep, Hale, Skinner, Hawkins, & Winn, 2007). There may be several contributing factors to this decrease in sensitivity as students' reading levels increase.…”
Section: Wcpmmentioning
confidence: 88%
“…RCR, designed to measure an individual's rate of comprehension, is often calculated by obtaining the comprehension number of percentage correct and multiplying this number/percentage by 60. This number is then divided by the number of seconds required to read the passages and finally multiplied by 100 (Freeland, Skinner, Jackson, McDaniel, & Smith, 2000;Neddenriep et al, 2007). Comprehension can be measured in a variety of ways, including multiple-choice comprehension questions and story retell.…”
Section: Wcpmmentioning
confidence: 99%
“…Marston (1989) described more than 10 studies that show that WC/M has strong concurrent validity. More recent studies also support the concurrent validity of WC/M with nonpublished reading comprehension measures, teacher judgments, and other valid and reliable standardized norm‐referenced reading measures (Hintze, Shapiro, Conte, & Baasile, 1997; Jenkins & Jewell, 1993; Neddenriep, Hale, Skinner, Hawkins, & Winn, 2007; Shinn, Good, Knutson, Tilly, & Collins, 1992). These studies have led researchers to characterize WC/M as a general outcome measure of reading skill development (Fuchs & Deno, 1991; Fuchs, Fuchs, Hosp, & Jenkins, 2001).…”
mentioning
confidence: 79%
“…The 2005 Nation's Report Card indicated that only 31% of fourth‐grade students could read at a proficient level (National Assessment of Educational Progress [NAEP], 2005). Additionally, the majority of special education referrals are for reading problems (Bramlett, Murphy, Johnson, Wallingsford, & Hall, 2002).…”
mentioning
confidence: 99%
“…An alternative would have been to allow students to continue to attempt to read words for an indefinite period of time, which could have invalidated the reading speed component of the reading comprehension rate measure as they spent inordinate amounts of time on individual words (Neddenriep et al, 2007). A more acceptable alternative would have been to tell students to skip the word and continue reading after a pause of 3-5 seconds.…”
Section: Discussionmentioning
confidence: 99%